2008
DOI: 10.1111/j.1399-3054.2008.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ammonium assimilation restores elongation of seminal rice roots repressed by high levels of exogenous ammonium

Abstract: Elongation of seminal and lateral roots of rice seedlings was markedly inhibited by high ammonium levels in growth medium. However, high exogenous nitrate concentrations had little inhibitory effect on root growth. The objective of this study was to elucidate the relationship between inhibition of rice root growth induced by high ammonium conditions and ammonium assimilation in the seedlings. Activity of glutamine synthetase (GS) was kept at a low level in the seminal roots of the seedlings grown under high ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…). The root growth was inhibited by 1.5 m M NH 4 + , which is similar to the observation of Hirano et al () using the same culture system (gel).Ammonium toxicity threshold may depend on the culture systems, because at the same concentration in the different medium, the ammonium availability is not the same for the plant. Root architecture plays an essential role in the efficiency of nutrient and water acquisition from soil (Lynch ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…). The root growth was inhibited by 1.5 m M NH 4 + , which is similar to the observation of Hirano et al () using the same culture system (gel).Ammonium toxicity threshold may depend on the culture systems, because at the same concentration in the different medium, the ammonium availability is not the same for the plant. Root architecture plays an essential role in the efficiency of nutrient and water acquisition from soil (Lynch ).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies reported that the seminal root elongation in rice was inhibited with increasing ammonium concentration in culture medium (Hirano et al ). Similarly, our data showed that excess NH 4 + significantly suppressed rice seedling growth, particularly in roots (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…GS activity is inhibited by methionine sulphoximine (MSO), resulting in elevated NH 4 + and reduced Gln levels (Lee et al , 1992; King et al , 1993; Hirano et al , 2008). This inhibitor was used to test whether NH 4 + metabolism is altered in vtc1-1 compared to the wild type when plants were grown in the presence or absence of NH 4 + .…”
Section: Resultsmentioning
confidence: 99%
“…Total glutamine synthetase activity was determined following a spectrophotometric assay (Mäck, 1995; Hirano et al , 2008). In brief, 30–60 mg tissue was extracted using 500 μl of an imidazole buffer consisting of 50 mM imidazole-HCl, 0.5 mM EDTA, 1 mM DTT, 10 mM MgSO 4 , and 1 mM phenylmethanesulphonyl fluoride.…”
Section: Methodsmentioning
confidence: 99%
“…metabolism, when inhibited, has been shown to result in elevated NH 4 ? levels and higher toxicity (Lee et al 1992;Kronzucker et al 1995;Hirano et al 2008). Indeed, the general view has emerged that plants with higher GS activity are more tolerant to NH 4 ?…”
Section: Discussionmentioning
confidence: 97%